Peran Pemerintah Kota Denpasar Dalam Mengakomodasi Hak Penyandang Disabilitas Dalam Memperoleh Pekerjaan - Komang Ema Marsitadewi; Ida Ayu Putu Sri Widnyani (Politicos: Jurnal Politik Dan Pemerintahan, 2021)
The existence of a disability label attached to a person with a disability makes it difficult for people with disabilities to find work. Whereas, in accordance with human rights, persons with disabilities should have the same rights as the general public in obtaining employment. Coupled with the existence of a legal umbrella in the protection and fulfillment of the rights of persons with disabilities in Bali, namely Regional Regulation No. 9 of 2015 concerning the Protection and Fulfillment of the Rights of Persons with Disabilities which can be the basis for fulfilling the rights of persons with disabilities in Bali. This includes the fulfillment of job rights for persons with disabilities. The method used is a qualitative method. Primary data were obtained by direct observation and field interviews with informants. While secondary data is obtained from reports related to persons with disabilities in accessing work. The results show that the government's role in the empowerment function is still weak. This can be seen from the training activities held by the Denpasar City Social Service and the Denpasar City Manpower Service. The training provided has varied, but due to budget constraints, it seems that the training provided is rare and underdeveloped for some people with disabilities. In addition, the lack of data collection causes the government to tend to invite only disability organizations. So that people with disabilities outside the organization are less aware of information related to the training provided by the government. This study recommends that the Denpasar City Social Service and Denpasar City Manpower Office improve socialization so that job providers will be more sensitive to the rights of persons with disabilities which should be the same as other communities in general.